2019 IEEE/AIAA 38th Digital Avionics Systems Conference (DASC) 2019
DOI: 10.1109/dasc43569.2019.9081718
|View full text |Cite
|
Sign up to set email alerts
|

Flight Demonstration of Unmanned Aircraft System (UAS) Traffic Management (UTM) at Technical Capability Level 3

Abstract: The goal of the Unmanned Aircraft System (UAS) Traffic Management (UTM) effort at NASA is to enable access to low-altitude airspace for small UAS. This goal is being achieved partly through partnerships that NASA has developed with the FAA, other government agencies, the UAS stakeholder community, and the designated FAA UAS Test Sites. This paper reports the technical and operational capabilities demonstrated during the UTM flight demonstration, March 6 through May 30, 2018. The demonstration featured geograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 10 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…The NASA flight demonstration for UTM technical capability level (TCL) 3 covered a sense and avoid scenario in which it addressed the hazard posed by transponder-equipped, manned flights. The scenario demonstrated the safe lateral separation in conflicts between a UAS using ADS-B IN and a manned flight using ADS-B OUT [42]. Similarly, another publication assessed separation between UAVs and manned flights equipped with ADS-B using commercial sensor equipment, called DJI AeroScope [43].…”
Section: Ads-b Researchmentioning
confidence: 94%
See 1 more Smart Citation
“…The NASA flight demonstration for UTM technical capability level (TCL) 3 covered a sense and avoid scenario in which it addressed the hazard posed by transponder-equipped, manned flights. The scenario demonstrated the safe lateral separation in conflicts between a UAS using ADS-B IN and a manned flight using ADS-B OUT [42]. Similarly, another publication assessed separation between UAVs and manned flights equipped with ADS-B using commercial sensor equipment, called DJI AeroScope [43].…”
Section: Ads-b Researchmentioning
confidence: 94%
“…The TCL 3 project verified a Remote ID broadcast operation in which UAVs were registered with UTM public key infrastructure (PKI) and broadcasted its messages. The messages were received properly and were identified by authorities on the ground [42]. The TCL 4 project demonstrated the capability of UTM-enabled Remote ID in several scenarios.…”
Section: Remote Id Researchmentioning
confidence: 99%
“…Consequently, the FAA established drone test sites in Alaska, Nevada, New York, North Dakota, Texas, and Virginia. The test sites supported the development and demonstration of Uncrewed Aircraft System (UAS) Traffic Management (UTM) systems [11]. The Northern Plains UAS Test Site in North Dakota has been demonstrating beyond visual line-of-sight (BVLOS) capabilities to support the practical commercial deployment of drones [12].…”
Section: Proving Facilitiesmentioning
confidence: 99%
“…This research has also identified problems that dense traffic in the low-level airspace will bring to the city users, by simulating the future urban airspace. In general, the functionalities of the aforementioned systems have only been demonstrated through simplistic simulations, and quite a few works have been devoted to field flight campaigns for preliminary tests [25,26]. We have also proposed in a previous work [27] a more realistic simulator for UAS operations based on the ROS middleware and the 3D simulation suite Gazebo (http://gazebosim.org, accessed on 26 April 2021).…”
Section: Related Workmentioning
confidence: 99%